2022
DOI: 10.1007/s13592-022-00950-5
|View full text |Cite
|
Sign up to set email alerts
|

How city traits affect taxonomic and functional diversity of urban wild bee communities: insights from a worldwide analysis

Abstract: Land-use change, including urbanization, is known to affect wild bee (Hymenoptera: Apoidea) diversity. However, while previous studies have focused on differences across local urbanization gradients, to the best of our knowledge, none focused on differences among cities at a wide geographical scale. We here used published data for wild bee communities in 55 cities across the globe, in order to explore how city traits (population density, city size, climate and land-use parameters) affect both taxonomic (divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…One explanation is assigned to the habitat fragmentation present in highly urbanised environments (suitable habitat patchily distributed) holding only a limited number of individuals (Swenson & Franklin, 2000). Albeit larger bees would be benefited from their ability to fly the longer distances needed to reach patches with greater foraging and nesting resources (Ferrari & Polidori, 2022; Theodorou et al, 2020). Thus, urban areas can act as environmental filters for small‐bodied bees whilst large‐bodied bees prosper (Ayers & Rehan, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation is assigned to the habitat fragmentation present in highly urbanised environments (suitable habitat patchily distributed) holding only a limited number of individuals (Swenson & Franklin, 2000). Albeit larger bees would be benefited from their ability to fly the longer distances needed to reach patches with greater foraging and nesting resources (Ferrari & Polidori, 2022; Theodorou et al, 2020). Thus, urban areas can act as environmental filters for small‐bodied bees whilst large‐bodied bees prosper (Ayers & Rehan, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also important to stress that the opposite can occur, and patchily distributed resources with higher isolation in cities might benefit large‐bodied bees and a female‐biased sex ratio. This is a consequence of adults capable of accessing distant yet rewarding patches as a consequence of their greater flight distance capabilities (Ferrari & Polidori, 2022; Greenleaf et al, 2007; Theodorou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Wilson and Jamieson (2019) determined that more urbanized sites supported a greater number of exotic, aboveground nesting, and solitary bees, but fewer eusocial bees. A study of bees in 55 cities across the globe explored how characteristics of cities influenced the taxonomic and functional trait profile of urban bees (Ferrari and Polidori, 2022). (Ferrari and Polidori, 2022) found that looking at the differences among cities across a wide geographical scale helped explain the previously observed variable response of some bee community traits across local urbanization gradients.…”
Section: Discussionmentioning
confidence: 99%
“…A study of bees in 55 cities across the globe explored how characteristics of cities influenced the taxonomic and functional trait profile of urban bees (Ferrari and Polidori, 2022). (Ferrari and Polidori, 2022) found that looking at the differences among cities across a wide geographical scale helped explain the previously observed variable response of some bee community traits across local urbanization gradients. They found, for example, that bigger cities host few parasitic and oligolectic species, along with more aboveground-nesting bees.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the important ecosystem service provided, bees (Hymenoptera: Apoidea)-the most important group of pollinators in cities (Lowenstein et al, 2015)-are increasingly receiving attention in the context of urbanization, though mostly from a community ecology point of view (e.g., Biella et al, 2022;Ferrari and Polidori, 2022;Geppert et al, 2023). Indeed, recent literature reviews clearly highlight the large amount of diversity and abundance data for urban bees accumulated in the last 20 years (e.g., Winfree et al, 2011;Wenzel et al, 2020;Brant et al, 2022;Ferrari and Polidori, 2022). On the other hand, there has been much less research published on the effect of urbanization-and in particular on the UHI effect-on bee functional traits (Buchholz and Egerer, 2020), spanning morphology, physiology, and behavior, among other traits (Brant et al, 2022).…”
Section: Introductionmentioning
confidence: 99%